Being bent over backward: A mother and teacher educator challenges the positioning of her daughter with disabilities - Leigh M. O'Brien (Disability Studies Quarterly, 2006)
In this paper I draw on my life story as a teacher educator and the mother of a daughter with disabilities to trouble the identity that positions and labels her as, first and foremost in U.S. school settings, a "child with special needs." Drawing on a brief snippet from our profoundly interrelated lives (Hillyer, 1993), I argue that educators must reconsider the positioning of children who differ from the "norm," and stop labeling, and hence limiting, children. I end with recommendations for personal, educational, and societal policies and practices that would be less painful and limiting, and more inclusive, supportive, and ultimately democratic.
Keywords: Disability; Special Education; Personal Narrative